Estimation of petrophysical data for assessing hydrocarbon potential in Western Ghana Oilfield (Tano Basin) - Kuffour, Opoku (2011)
A report submitted to the school of Graduate Studies, Kwame Nkrumah University of Science and technology (KNUST), Kumasi, in partial fulfillment of the Degree of Msc. Geophysics.